2005
DOI: 10.1016/j.bbr.2005.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Age-related qualitative shift in emotional behaviour: Paradoxical findings after re-exposure of rats in the elevated-plus maze

Abstract: Several variables, including age, are known to influence anxiety. Previous exposure to the elevated-plus maze (EPM) is known to modify emotional behaviour as retesting in the EPM at a standard age of 3 months increases open-arm avoidance and attenuates the effects of anxiolytic drugs. This study analysed whether similar results are obtained when older animals are subjected to these experimental paradigms. Overall, increasing age was associated with more signs of anxiety. Additionally, we observed a paradoxical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 43 publications
(57 reference statements)
3
15
0
3
Order By: Relevance
“…In the plus-maze, our data suggest a decrease in anxiety-related behavior over aging, in agreement with previous studies (Pisarska et al 2000;Torras-Garcia et al 2005, but Boguszewski andZagrodzka 2002;Bessa et al 2005). As this decrease was not observed in middle-aged rats, it is probably not a phenomenon protracting over lifespan.…”
Section: Emotional Behaviorssupporting
confidence: 93%
“…In the plus-maze, our data suggest a decrease in anxiety-related behavior over aging, in agreement with previous studies (Pisarska et al 2000;Torras-Garcia et al 2005, but Boguszewski andZagrodzka 2002;Bessa et al 2005). As this decrease was not observed in middle-aged rats, it is probably not a phenomenon protracting over lifespan.…”
Section: Emotional Behaviorssupporting
confidence: 93%
“…In addition, the elevated plus maze yields data on locomotor activity, vertical activity and exploratory behavior and provides indices of risk assessment and decision making (Rodgers & Dalvi 1997). Recent studies have shown that age (Bessa et al 2005), familiarity with the experimenter (van Driel & Talling 2005) and the gradient of luminosity between open and closed arms (rather than the absolute illumination strength) (Pereira et al 2005) have an important influence on the outcome of the elevated plus maze test.…”
Section: Exploratory and Emotional Behaviormentioning
confidence: 99%
“…These factors include individual differences in overall anxiety levels (Ho et al, 2002), gender (Imhof et al, 1993), illumination levels (Garcia et al, 2005;Pereira et al, 2005), strain (Bert et al, 2001;Chaouloff et al, 1995;Ramos et al, 1997), and experience in the maze (Bessa et al, 2005;File, 1993;Gallagher and Pelleymounter, 1988). The specific factors that might have elicited the preference for the open arms of the maze in the younger rats in the present experiment cannot be determined.…”
Section: Discussionmentioning
confidence: 81%
“…Previous research has shown that there are consistent changes in the amount of time spent in the open arms of the maze as a function of age. As the age of the rats increases, there is a corresponding decrease in the amount of time spent exploring the open arms of the maze (Andrade et al, 2003;Baguszewski and Zagrodzka, 2002;Bessa et al, 2005;Imhof et al, 1993).…”
Section: Introductionmentioning
confidence: 98%